Perencanaan Program Ruang Unit Hunian berbasis Persepsi Pengguna Rumah Susun Kota Palembang (Universitas Muhammadiyah Palembang, 2023)
Flats are a type of vertical housing which has begun to be intensively developed and has become the choice of place for people to live in Palembang. However, many architectural problems have arisen in the flats of Palembang city. This problem is in the form of spatial deviation because its function is randomly adjusted to the needs of residents. This study aims to identify spatial program formulations that can be applied to flats planning based on user perceptions. The research method uses a combination method (mixed-methods), namely solving problems with significant data sets through a quantitative approach and testing subjects dynamically based on a qualitative approach. The results of the study show that the application of user perceptions generates new space categories that are most likely to be applied to the planning process. The space category appears when several common spaces are separated in flat housing units. From this study it can also be concluded that the planning of flats based on user perceptions can be used as a benchmark for the desire of flat occupants to improve environmental and social quality within their environmental line.